Fifty-odd years of inter-group contact: from hypothesis to integrated theory. - Hewstone, M; Swart, H (2011)
We review 50-odd years of research on Allport's (1954)'contact hypothesis', to assess progress, problems, and prospects. We chart the progress that has been made in understanding two distinct forms of contact: direct and indirect. We highlight the progress made in understanding the effects of each type of contact, as well as both moderating and mediating factors, and emphasize the multiple impacts of direct contact, especially. We then consider some of the main critiques of inter-group contact, focusing on empirical issues and whether contact impedes social change, and provide a research agenda for the coming years. We conclude that this body of work no longer merits the modest title of 'hypothesis', but fully deserves acknowledgement as an integrated and influential theory.